Increasing Students’ Motivation in Learning English Through Quizizz at Tenth Graders Of SMK Negeri 1 Ulumoro’o - Puspa Fati Handayani Gulo; Elwin Piarawan Zebua; Adieli Laoli; Afore Tahir Harefa (Institut Agama Islam Negeri (IAIN) Manado, 2026)
This study aims to determine how a quizzes application can increase students' learning motivation in the tenth grade at SMK Negeri 1 Ulumoro'o. The method used was Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were obtained through pre-test and post-test. The population in this study consisted of all tenthgrade students at SMK Negeri 1 Ulumoro'o. The sample was selected using the following method. Researchers generally use the cluster sampling method. The study demonstrates that Quizizz application substantially boosts student learning motivation and performance, as evidenced by the progressive rise in average scores from Cycle I (64.73) to Cycle II (86.84). This improvement aligns with action research cycles, where iterative application resolves initial motivation deficits in tenth-grade students at SMK Negeri 1 Ulumoro'o.Keywords: motivation, learning motivation, quiziz app, classroom action research.